Incidencia de Flebitis en Neonatos, en el Hospital Teófilo Dávila, Machala – Ecuador - Reyes Rueda, Elida Yesica; Arteaga de Vizcaíno, Melvis; García Maldonado, Jorge Armando; ChambaTandazo, Marlene Johana; García-Bastidas, Laura Belén (My University, 2021)
The purpose of this research was to determine the incidence of phlebitis in neonates, at the Teófilo Dávila Hospital, in the city of Machala - El Oro - Ecuador. A non- experimental, cross-sectional,qualitative, descriptive and observational field study was carried out. Statistical analysis was performed using SPSS version 24; For the preparation of tables and graphs, the Microsoft Excel 2010 program was used. The population that was the reason for this was constituted by 65 neonates admitted to the area of neonatology, intermediate care unit and neonatal intensive care unit, with a gestational age between The 28 SG to 42.5 SG, with an average age of 36 SG with a standard deviation of ± 4. 64.62% were male and 35.38% female. In conclusion, the incidence of phlebitis in neonates admitted to the neonatology area of Teófilo Dávila Hospital was 44.62%, of which 79.31% had grade 1 phlebitis; and 20.69% grade 2 phlebitis. 89.6% experienced phlebitis 1 time and 10.34% 2 times.
El propósito de esta investigación fue determinar la incidencia de flebitis en neonatos, en el Hospital Teófilo Dávila, de la ciudad de Machala – El Oro – Ecuador. Se realizó un estudio de campo, no experimental, de corte transversal, de tipo cualitativo, descriptivo y observacional. El análisis estadístico se realizó mediante el programa SPSS versión 24; para la elaboración de tablas y gráficos se usó el programa Microsoft Excel 2010. La población motivo del estuvo, estuvo constituida, por 65 Neonatos ingresados en el área de Neonatología, Unidad de Cuidados Intermedios y Unidad de Cuidados Intensivos Neonatales, con una edad gestacional entre las 28 SG a 42.5 SG, con una edad promedio de 36 SG con una desviación estándar de ± 4. El 64.62%, eran de sexo masculino y el 35.38% femenino. En conclusión, la incidencia de flebitis en los neonatos ingresados en el área de neonatología del Hospital Teófilo Dávila, fue del 44.62%, de los cuales el 79.31% presentó flebitis grado 1; y, el 20.69% flebitis grado 2. El 89.6% experimentó flebitis 1 vez y el 10.34%, 2 veces.
Keywords: FACTORES DE RIESGO; FLEBITIS; NEONATO; CATETER; HOSPITALIZACION.